Investigating the molecular basis of multiple insecticide resistance in a major malaria vector Anopheles funestus (sensu stricto) from Akaka-Remo, Ogun State, Nigeria - Atoyebi, Seun M.; Tchigossou, Genevieve; Akoton, Romaric; Riveron, Jacob M.; Irving, Helen; Weedall, Gareth (BioMed Central, 2020)
Understanding the mechanisms used by Anopheles mosquitoes to survive insecticide exposure is key to manage existing insecticide resistance and develop more suitable insecticide-based malaria vector control interventions as well as other alternative integrated tools. To this regard, the molecular basis of permethrin, DDT and dieldrin resistance in Anopheles funestus (sensu stricto) at Akaka-Remo was investigated.